2018
DOI: 10.1155/2018/6180810
|View full text |Cite
|
Sign up to set email alerts
|

Use of Jianpi Jiedu Herbs in Patients with Advanced Colorectal Cancer: A Systematic Review and Meta‐Analysis

Abstract: Objective To systematically review the effect of invigorating Pi and detoxification (Jianpi Jiedu, (JPJD)) herbs in advanced colorectal cancer (CRC) patients receiving chemotherapy. Methods Three English and four Chinese databases were searched. Literature was screened by EndNote X7 and data were analyzed by RevMan 5.2. Results This review comprised 12 randomized clinical studies of 701 patients. The results showed that JPJD herbs improved the therapeutic effect on Chinese medicine symptoms [risk ratio (RR) = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Our study is in general accord with prior research (19, 30, 31). Nie et al (12) have reported a relatively satisfactory result by using a radiomics method, with an AUC of 0.84 for pCR and 0.89 for good response prediction.…”
Section: Discussionsupporting
confidence: 91%
“…Our study is in general accord with prior research (19, 30, 31). Nie et al (12) have reported a relatively satisfactory result by using a radiomics method, with an AUC of 0.84 for pCR and 0.89 for good response prediction.…”
Section: Discussionsupporting
confidence: 91%
“…41,42 Therefore, when we encounter elderly patients, minimally invasive therapies such as laparoscopic surgery could help reduce surgical trauma, and Chinese herbs can relieve and reduce the adverse events of chemotherapy. 43 For NETs in the colon, the recommended treatment varies among different guidelines, but surgical resection is generally recommended because of the greater likelihood of malignant behavior than with rectal NETs. Endoscopic resection may be considered if the tumor diameter is less than 2 cm and does not reach the muscularis propria.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer treatment with chemical agents is destructive to malignant cells and tissues, as well as nontumor tissues. TCM theory holds that the toxicity of chemotherapy may lead to an imbalance of Qi and blood, dysfunction of the viscera, and increased accumulation of pathogenic factors such as toxic heat blood stasis in the body [ 59 ].…”
Section: Discussionmentioning
confidence: 99%